From the Outskirts to the Heart of Peacebuilding? The march of women in the United Nations’ peacebuilding regulation - Koski, Veera (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis examines the United Nations’ (UN) regulation on women’s position and roles in the peacebuilding context. In the case study part, the roles identified in the regulation are analyzed in an onsite peacebuilding project. The study has its emphasis on the thematic resolutions in the field of “women, peace and security” issued by the UN Security Council. The resolutions indicate that women’s position in peacebuilding is important for the realization of their human rights and for maintaining international peace and security. In spite of the development, the resolutions have been subject to serious criticism. In particular, the critical remarks have brought forward the underlying structural challenges and restricted roles that the resolutions assign to women. Both legal dogmatics and sociology of law are applied in the thesis through academic literature. An interview has been used as a source for the case study. The thesis reflects feminist legal theories, which have had an impact on the motivation behind this thesis, interpretation of the nature of international law, methodology and results. In addition, critical views concerning human rights have been presented. The thesis is based on the dialogue between the views that support the resolutions and the views that have taken a more critical stand towards them. The roles women are assigned in the resolutions are measured against these different views. The case study examines how the roles identified in the resolutions are presented in practice, in conjunction with a selected peacebuilding project. The global West-South divide as well as the deeply rooted structural masculinity are stressed especially in the critique. The thesis brings forward the idea of how the selected approach impacts the assessment of the resolutions and their opportunities to empower women in the peacebuilding context. The findings, aligned with the feminist legal views, indicate that the resolutions present only limited opportunities to promote women’s position in the peacebuilding context. In addition, the roles assigned to women appear restricted. The resolutions cannot escape the historical ties that are maintained by international institutions, inter alia the UN. The resolutions have, however, striven towards a good cause – to empower women and strengthen their multiple roles – and it is possible to withdraw from the colonialist and masculine ties in peacebuilding work. A more thorough reconstruction of international law and its institutions is needed to empower women. The current crossroads of global institutionalization may bring opportunities to empower change. The resolutions can be used in promoting women’s position, but they should not constitute the sole means.